Extensive Amyloid Purpura: An Unusual Presentation of Myeloma-associated Light Chain Amyloidosis - Nor Fazil Jaber; Ulrika Thelander; Philip Curman (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)